Cyclization of Active Methylene Isocyanides with α-Oxodithioesters Induced by Base: An Expedient Synthesis of 4-Methylthio/Ethoxycarbonyl-5-acylthiazoles - Kiran, Kuppalli R.; Swaroop, Toreshettahally R.; Rajeev, Narasimhamurthy; Anil, Seegehalli M.; Rangappa, Kanchugarakoppal S.; Sadashiva, Maralinganadoddi P. (Synthesis, 2020)
Cyclization of tosylmethyl isocyanide with α-oxodithioesters in the presence of KOH is reported for the synthesis of 4-methylthio-5-acylthiazoles. Similarly, ethyl isocyanoacetate underwent cyclization with α-oxodithioesters to form 4-ethoxycarbonyl-5-acylthiazoles in the presence of DBU/EtOH. Mechanisms for the formation of thiazoles are proposed. These thiazoles can also be obtained by Takeda reaction, in which thiazole-4,5-anhydride is acylated with aromatic compounds followed by esterification; however, that approach requires two steps and suffers from the formation of a regioisomeric mixture of products.
Keywords: thiazole; TosMIC; ethyl isocyanoacetate; α-oxodithioester; cyclization